Radiation induces ESCRT pathway dependent CD44v3+ extracellular vesicle production stimulating pro-tumor fibroblast activity in breast cancer - Clark, Gene Chatman; Hampton, James David; Koblinski, Jennifer E.; Quinn, Bridget; Mahmoodi, Sitara; Metcalf, Olga; Guo, Chunqing; Peterson, Erica; Fisher, Paul B.; Farrell, Nicholas P.; Wang, Xiang-Yang; Mikkelsen, Ross B. (Frontiers in Oncology, 2022)
Despite recent advances in radiotherapeutic strategies, acquired resistance remains a major obstacle, leading to tumor recurrence for many patients. Once thought to be a strictly cancer cell intrinsic property, it is becoming increasingly clear that treatment-resistance is driven in part by complex interactions between cancer cells and non-transformed cells of the tumor microenvironment. An enhanced understanding of these interactions may provide novel avenues for enhancing radiotherapy. Here we report that radiotherapy induces the production of extracellular vesicles by breast cancer cells capable of stimulating tumor-supporting fibroblast activity, facilitating tumor survival, and promoting cancer stem-like cell expansion. This pro-tumor activity was associated with production of the paracrine signaling factor IL-6 and was dependent on the expression of the heparan sulfate proteoglycan CD44v3 on the vesicle surface. Enzymatic removal or pharmaceutical inhibition of its heparan sulfate side chains disrupted this tumor-fibroblast crosstalk. Additionally, we show that the radiation-induced production of CD44v3+ vesicles can be effectively silenced by blocking the ESCRT pathway using a soluble pharmacological inhibitor of MDA-9/Syntenin/DCBP PDZ1 domain activity, PDZ1i. This population of vesicles was also detected in the sera of human patients undergoing radiotherapy, therefore representing a potential biomarker for radiation therapy and providing an opportunity for clinical intervention to improve treatment outcomes.